Data for the paper "Analysis of Autopilot Disengagements Occurring during Autonomous Vehicle Testing" - Lyu, Chen; Cao, Dongpu; Zhao, Yifan; Auger, Daniel; Sullman, Mark; Wang, Huaji (Cranfield University, 2017)
Data used in the paper "Analysis of Autopilot Disengagements Occurring during Autonomous Vehicle Testing".
Keywords: Disengagement'; 'Autonomous Vehicle Testing'; 'Autonomous Vehicles'